The Criteria And Challenges Of Unethical Advertising - Mohammad Noorizzuddin Nooh; Khairil Faizal Khairi; Muhammad Ridhwan Ab. Aziz; Rabi’atul ‘Adawiyah binti Rashiddi; Syadiyah Abdul Shukor; Mahdhir Abdullah (Open Science, 2024)
Non-Indexed Publication